PERKEMBANGAN OTONOMI DAERAH DAN PROBLEMATIKA PENERAPANNYA DI SUSUN UNTUK MEMENUHI TUGAS MATA KULIAH: HUKUM PEMERINTAHAN DAERAH DAN OTDA - Azzura Gladisya; Ade Yuni Sihombing; Puja Silvia (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Regional autonomy is a system or an authority owned by a region. The purpose of the establishment of regional autonomy is to develop the area and the contents that exist within the area. Regional autonomy is the independence of a region where the independence is closely related to making and making decisions about important matters within the region itself. Regional autonomy can also be interpreted as a regional autonomy authority. This authority is used to regulate and manage the interests of the local community in the autonomous region. This is based on the procedures for its own implementation and based on the aspirations taken from the community. In Law Number 32 of 2004 Article 1 number (5) explains that "Regional autonomy is the right, authority, and obligation of an autonomous region to regulate and manage its own government affairs and the interests of the local community in accordance with statutory regulations."